Latent profiles of post-traumatic growth in patients with recent hysterectomy: psychosocial predictors and stigma-associated outcomes - Sun, Yuqing; Wu, Shirong; Zou, Qunfeng; Fu, Xiuzhen; Liu, Silu; Chen, Gongna; Zheng, Xiaojie; Qiu, Dingrong (Frontiers in Psychiatry, 2025)
BackgroundStudies have found that post-traumatic growth exists in patients with recent hysterectomy. However, previous studies have overlooked heterogeneity within groups. There is a lack of research on whether there are different categories of post-traumatic growth levels in patients with recent hysterectomy. Therefore, this study explores different categories of post-traumatic growth and their influencing factors in patients with recent hysterectomy based on latent profile analysis. It also analyses the relationship between stigma and different profiles of post-traumatic growth in patients.MethodsThis study, which used convenience sampling to select patients who underwent hysterectomy at the gynaecology department of a tertiary hospital in Guangzhou, Guangdong Province, was conducted from February to September 2024. The study included 210 patients aged 18 years or over who had undergone a hysterectomy and had agreed to participate in the questionnaire survey. A total of 210 questionnaires were distributed and 202 valid responses were received. The study used the following scales: a general information questionnaire (covering patients’ sociodemographic and clinical characteristics); post-traumatic growth inventory-Chinese version (C-PTGI); and social impact scale (SIS). The C-PTGI primarily measures the level of posttraumatic growth in patients with recent hysterectomy; higher total scores indicate greater posttraumatic growth. The SIS assesses the level of stigma experienced by patients with recent hysterectomy, with higher scores indicating a greater degree of stigma. The data were analysed using SPSS 25.0 and Mplus 8.3.ResultsPost-traumatic growth in patients with recent hysterectomy consisted of 3 types: negative growth group (18%), low-transformation-moderate growth group (53%), and positive growth group (29%). Significant differences in post-traumatic growth and scores on each dimension were found in different subgroups (P < 0.05). Patients with recent hysterectomy aged 40–59 were more likely to be classified as belonging to the positive growth group. Those with high scores on the internalized shame and social isolation dimensions were more likely to belong to the negative growth group. Compared with the positive growth group, educational attainment at elementary or junior high school level was a predictor of belonging to the low-transformation-moderate growth group.ConclusionHeterogeneity exists in the post-traumatic growth level of patients with recent hysterectomy. Younger patients with higher levels of education and lower scores on the SIS tend to experience better post-traumatic growth after hysterectomy. Healthcare professionals should adopt more flexible and targeted interventions to help patients enhance their post-traumatic growth levels under the premise of correctly identifying the characteristics of different potential categories. This can better improve the mental health status of patients, promote their postoperative recovery, and enhance their quality of life and satisfaction.